OSMASA (Mawaridussalam Student Organization): Leadership in Islamic Education at Islamic Boarding School - Budiman, Agus; Choirunnisa, Akasyah Kunthum; Maha, Marheni Br; Fauziah, Siti Anne Barkah Nur; Al-Askary, Azkiyatul Adawiyah Farid Hasem (Al-Tadzkiyyah: Jurnal Pendidikan Islam, 2023)
The quality of a nation can be seen from the quality of education applied to it. In an effort to create human resources with noble character, leadership education is needed to form a caliph on this earth. Leadership education has an important role in the life of society and the state because it is the leader who will manage everything in it so that there will be no chaos and disputes between one another. This research is a qualitative descriptive study. While the approach used is a case study approach to intensively study the role of OSMASA as a means of leadership education for male and female students at the Mawaridussalam Islamic Boarding School, this organization is under the guidance of supervisors from each section. The subjects of this study were all male and female students of grade 5 KMI who served as OSMASA administrators. Data collection was carried out through interviews, documentation, and field observations. The results of this study state that OSMASA can be used as a means to improve the leadership spirit of students at the Mawaridussalam Islamic Boarding School. This can be seen from the various 24-hour activities that are organized in such a way and carried out with full discipline and exemplary behavior. Thus, this study aims to determine the role of OSMASA in creating students who are independent, responsible, sensitive to the environment, and have noble character. So that students are expected to be able to become leaders in the future that are useful for the nation and religion.